Influence of ion-beam treatment on structure and defor-mation resistance of 12Cr1MoV steel under static, cyclic and dynamic loading; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Panin S. V. Sergey Viktorovich; Vlasov I. V. Ilya Viktorovich; Maruschak P. O.; Sergeev V. P. Viktor Petrovich (Materials and technologies new generations, 2015)
Title screen